Wages, experience and seniority - Christian Dustmann; Costas Meghir (Institute for Fiscal Studies (IFS), 2001)
In this paper we study the sources of wage growth. We identify the contribution to such growth of general, sector specific and firm specific human capital. Our results are interpretable within the context of a model where the returns to human capital may be heterogeneous and where firms may offer different combinations of entry level wages and firm specific human capital development. We allow for the the possibility that wages are match specific and that workers move jobs as a result of identifying a better match. To estimate the average returns to experience, sector tenure and firm specific tenure within this context, we develop an identification strategy which relies on the use of establishment closures. Our data source is a new and unique administrative data set for Germany that includes complete work histories as well as individual characteristics. We find positive returns to experience and tenure for skilled workers. The returns to experience and tenure for unskilled workers are substantially lower.
Keywords: 330; Training; labour market; wages; Lohn; Lernprozess; Betriebszugehörigkeit; Humankapital; Senioritätsentlohnung; Arbeitsmobilität; Theorie; Deutschland; USA